Thermal behavior of aluminum metal-matrix composite during cooling process - Okumus, F.; Turgut, A. (American Society of Mechanical Engineers (ASME), 2001)
The paper presents a thermal behavior analysis of metal matrix composite lamina and laminates during a cooling process.A long stainless steel fiber reinforced aluminum metal matrix composite lamina and laminate are used for this purpose. Metal matrix composites were manufactured by using modulus under the action of 30 MPa pressure and heating up to 600 °C. The thermal stresses generated during cooling have a profound effect on the distortion and strength of the composite materials. In this study, thermal stresses, residual stresses and effective thermal expansion coefficients as a function of orientation angle of the aluminum metal matrix composite during a cooling process are investigated. The finite element method was used for thermal stress analysis. For this purpose, four noded rectangular elements were used in the ANSYS finite element code. Copyright © 2001 by ASME
ASME 2001 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference, IDETC-CIE 2001 -- 9 September 2001 through 12 September 2001 -- Pittsburgh -- 164952
Keywords: Aluminum; Aluminum coated steel; Cooling; Design; Finite element method; Laminated composites; Metal analysis; Paper laminates; Reliability analysis; Steel fibers; Stress analysis; Thermal expansion; Thermal stress; Aluminum metal matrix composites; Ansys finite elements; Cooling process; Heating up; Metal matrices; Orientation angles; Thermal behaviors; Thermal expansion coefficients; Metallic matrix composites